Use of the Biofeedback Method in Sports and Pre-Competition Procedures (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Biofeedback is a psychological and physiological technique that involves the use of visual or auditory aids to teach people to recognize physical signs and symptoms of stress and anxiety, such as heart rate, body temperature, and muscle tension. With the help of biofeedback tool, athletes can understand the autonomic nervous system in advance and conduct standardized sports training. Feedback information, which not only significantly improves the body's ability to control the nervous system, but also ensures the health of athletes, lays the foundation for a good effect of exercise.